Brief Documentation of Land and Water Ecosystem in Kubah and Santubong National Parks, Sarawak - Mohamad Fhaizal, Mohamad Bukhori; Rohaiza, Daud; Christharina, S Gintoron; Muhamad Ikhwan, Idris; Roberta Chaya Tawie, Tingga; Mohd Ridwan, Abd Rahman; Anang Setiawan, Achmadi (Universiti Pendidikan Sultan Idris, 2025)
Kubah and Santubong National Parks are among Sarawak’s heritage ecological treasures, featuring diverse land and water ecosystems that are vital to state and national biodiversity. The conservation and preservation of these parks is crucial for maintaining the sustainability of the environment and ensuring that future generations can continue to benefit from their natural beauty and resources. The parks are significant natural reserves, exhibiting unique landscapes including lush tropical rainforests and aquatic environments. Kubah National Park ecosystem includes dipterocarp trees, ferns, fungi, and detritivores, and insects; meanwhile, Santubong National Park ecosystem includes mountainous terrain, dipterocarp trees, invertebrates, and ferns. Thus, to effectively comprehend and promote conservation and preservation efforts, we have to experience biodiversity and ecology and impart to differentiate different components of the ecosystem. Therefore, a field work was conducted to experience the biodiversity and ecology of discerned organisms in various ecosystems in Kubah and Santubong National Park. The input was analysed and described selected ecosystems, plants, and animals and referred to previous scientific reports from various resources. Experiences with biodiversity and ecology are vital for future development, especially in the realms of academics, research, development, and lifelong learning, all contributing to a sustainable future.